Intervention I: Neighbors - Voyer, Andrea (Cross currents, 2017)
The article focuses on a report of the Office of the United Nations High Commissioner for Refugees (UNHCR) on migration in Somalia. It mentions that U.S. President Donald Trump administration's travel ban has barred U.S. visas to all Somali passport holders. It offers suggestions for migrants regarding gaining freedom for immigrants to define their place in the social structure; un- and under-developed immigration services; and less social isolation.